The level of digitization of the information society in EU countries as a determinant of the use of official statistics - Becker, Aneta (Badanie poziomu cyfryzacji społeczeństwa informacyjnego w krajach UE jako determinanta wykorzystania statystyki publicznej, 2020)
The development of ICT and information culture has meant that the expectations of information recipients have changed, the more so that these technologies have permanently penetrated into many areas of life. This is expressed by the need to educate and activate those interested so that they can participate in the changing socio-economic reality. The article discusses the role of official statistics in socio-economic life and its impact on the information society. The challenges awaiting today and the participation of new technologies in the implementation of these projects were presented. The paper also presents the results of the classification study of EU countries according to the degree of digitization of society, obtained using the ELECTRE TRI method. The study used empirical material that came from the resources of the European Statistical Office (Eurostat). The results of multi-criteria analysis confirmed that EU residents are active users of the global Internet network. In terms of the use of ICT services, there are disproportions between EU countries
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 6, s. 23-37